Experimental and Archival Research in Auditing: Complementarities, Convergence, and Future Directions - Nelson, Mark W. (The Accounting Review, 2025)
ABSTRACT This commentary considers experimental and archival auditing research published over the past 50 years and suggests directions for future research. Starting with Ashton (1974a) and Simunic (1980), I discuss major research themes occurring in these literatures. I use Brunswik’s lens model as a metaphor that highlights methodological complementarities and opportunities for convergence to address important issues. Possible topics to consider further in future research include the determinants of audit quality, the structure of audit firms and audit regulation, the effect of emerging technologies like AI, teaching and supporting future auditors, potential enhancements of the audit report, and expansion of the services that auditors provide to society.